2017
DOI: 10.1080/19440049.2017.1384576
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the content of TiO2 nanoparticles in the coatings of chewing gums

Abstract: Titanium dioxide is a metal oxide used as a white pigment in many food categories, including confectionery. Due to differences in the mass fraction of nanoparticles contained in TiO, the estimated intakes of TiO nanoparticles differ by a factor of 10 in the literature. To resolve this problem, a better estimation of the mass of nanoparticles present in food products is needed. In this study, we focused our efforts on chewing gum, which is one of the food products contributing most to the intake of TiO. The coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 15 publications
1
32
0
Order By: Relevance
“…In turn, this ensured representative sampling and avoided biased measurements due to agglomeration and particle overlap. It resulted in higher fractions of nanosized particles (<100 nm) than those reported in several publications [6,7,9,42,43,53,56,57], where these factors were less well controlled. Geiss et al consider such optimization as essential for the development of validated and harmonized sample preparation protocols [55].…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…In turn, this ensured representative sampling and avoided biased measurements due to agglomeration and particle overlap. It resulted in higher fractions of nanosized particles (<100 nm) than those reported in several publications [6,7,9,42,43,53,56,57], where these factors were less well controlled. Geiss et al consider such optimization as essential for the development of validated and harmonized sample preparation protocols [55].…”
Section: Discussionmentioning
confidence: 55%
“…In addition to the EFSA opinion, several studies characterized commercially available pristine E171 materials and food products containing E171 [6,7,9,42,43,52,[56][57][58]. In general, mean particle sizes between 106 and 145 nm and size distributions ranging from 30 nm to 400 nm were reported for electron microscopy (EM) analyses [6,9,42,43,[56][57][58]. One study showed a size distribution ranging from 30 to 600 nm for scanning electron microscopy (SEM) and 20 to 400 nm for asymmetric flow field-flow fractionation coupled with inductively coupled plasma mass spectrometry (AF4-ICP-MS) [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ANS Panel at the European Food Safety Authority (EFSA) proposes to use a proportion of 3.2% by mass to estimate the nano-sized fraction of E 171 for risk assessment considerations [ 13 ]. TEM analyses of TiO 2 particles in the coatings of chewing gums revealed a nano-sized mass fraction of 4.2% on the average [ 45 , 46 ]. This review only includes studies where TiO 2 test materials have been characterized with respect to their size preferably with indications on the primary particle diameter.…”
Section: Introductionmentioning
confidence: 99%
“…The ROS can then synergistically act by attacking polyunsaturated phospholipids in bacteria and catalyzed site-specific DNA damage via generation of H 2 O 2 [61]. TiO 2 nanoparticles have been used as whitening agent, food additive (E171) and a drug delivery vehicle [62,63]. TiO 2 nanotubes are potential to be used as a drug vehicle in the area of nanomedicine, like for bone regeneration or cancer therapy [64].…”
Section: Nanomaterialsmentioning
confidence: 99%